Efficacy and safety of radiotherapy combined with immunotherapy and targeted therapy versus immunotherapy plus targeted therapy alone in unresectable hepatocellular carcinoma: a retrospective study - Yuan, Yanling; Chen, Yongsheng; Huang, Chumin; Liu, Mindong; Tong, Lihua; Tang, Wubing; Yang, Wen (Frontiers in Oncology, 2025)
PurposeTo evaluate the efficacy and safety of radiotherapy combined with immunotherapy and targeted therapy (RT+IO+T) versus immunotherapy plus targeted therapy alone (IO+T) in patients with unresectable hepatocellular carcinoma (HCC). Given the limited prospective evidence supporting the integration of radiotherapy into systemic regimens, particularly in real-world populations with advanced disease, this study aims to clarify the clinical value of this multimodal approach.MethodsThis retrospective study analyzed 71 patients with unresectable HCC treated between 2020 and 2025. Patients received either IO+T (n=42) or RT+IO+T (n=29), including immune checkpoint inhibitors (ICIs) (e.g., camrelizumab), targeted agents (e.g., lenvatinib), and RT. Outcomes were assessed using the modified Response Evaluation Criteria in Solid Tumors (mRECIST) criteria. Survival analysis was performed using Kaplan–Meier and Cox regression models.ResultsCompared with the IO+T group, the RT+IO+T group demonstrated superior short-term efficacy, as indicated by the objective response (69.0% vs. 35.7%, p=0.006) and disease control (89.7% vs. 57.1%, p=0.003) rates. Additionally, the median progression-free survival (PFS) and overall survival (OS) were significantly prolonged in the RT+IO+T group compared with the IO+T group (PFS: 12.6 vs. 4.6 months, p<0.001; OS: 17.8 vs. 10.9 months, p=0.009). Subgroup analyses confirmed consistent survival benefits across patient characteristics. However, the RT+IO+T group showed increased hematologic toxicity (grade ≥3 lymphopenia: 62.1% vs. 19.0%, p<0.001) and hepatic enzyme elevation (aspartate aminotransferase: 75.9% vs. 35.7%, p<0.001).ConclusionAdding RT to IO+T significantly improved tumor response and survival in unresectable HCC, despite higher manageable hematologic and hepatic toxicities.Clinical significanceThe results of this study support RT+IO+T as a promising strategy for advanced HCC, particularly in patients with high tumor burden or portal vein invasion. The synergistic effect of RT, immunotherapy, and target therapy highlights its potential to redefine treatment paradigms, although toxicity monitoring remains critical.